Evaluasi Kemampuan Literasi Biodiversitas Mahasiswa - Fajri, Siti Rabiatul; Citrawathi, Desak Made; Adnyana, Putu Budi; Arnyana, Ida Bagus Putu (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Indonesia is one of the countries with the highest biodiversity in the world. However, this high diversity requires individual awareness and responsibility to maintain and utilize it sustainably. Therefore, biodiversity literacy is an important element, especially for students as prospective future generations who will play a role in natural resource management in the future. This study aims to evaluate the level of biodiversity literacy of students of the Biology study program at the University of Education Mandalika, by assessing six dimensions of biodiversity literacy: Conservation and Importance of Biodiversity (CIB), Ethics and Biodiversity (EB), Sustainability and Biodiversity (SB), Taking Action to Protect Biodiversity (TAPB), Biodiversity and Utility (BU), and Conservation and Importance of Species (CIS).Â The method used was quantitative descriptive, involving 50 students as respondents. The instrument used consisted of 27 items that were analyzed using One Way ANOVA to determine the average score and significant differences based on gender and student scores. The results showed that the average score of biodiversity literacy obtained a score of 2.08 with a less significant category (Low Biodiversity Literacy). Most of the indicators are at an average value below 2.50, only a small number of indicators have an average value above 2.50. In the CIB dimension, only 3 indicators have an average value of > 2.50 out of 5 indicators. In the TAPB dimension, only 1 indicator has an average > 2.50. While in other dimensions, the average value < 2.50. In addition, there was no significant difference in student scores based on gender. Thus, student biodiversity literacy still needs to be improved, especially in the aspects of real action and individual responsibility.